The Role of Social Media in Improving the Quality of Public Services in the Covid-19 Era at the Ombudsman Office in Makassar City - Rasmi Rasmi; Andi Rosdianti Razak; Muhammad Yahya (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2022)
This study explains the quality of Makassar City Ombudsman Public Service through Social Media in the Covid-19 Era. The impact of the Covid-19 pandemic requires online-based services and is carried out through social media. This study aims to examine and describe the role of social media in improving the quality of public services at the Makassar City Ombudsman office seen in indicators of the quality of public services, namely transparency, accountability, coordination, participation, equality of rights and continuity between rights and obligations. This research uses qualitative research methods with descriptive research type. Collecting data using observation, interviews, documentation and media review. The results of this study are that the role of social media in improving the quality of public services seen from the aspects of transparency, accountability, coordination, participation, equality of rights and continuity of rights and obligations has been going well and is considered to have been maximized by the community. It can be concluded that social media has an important role to improve the quality of effective public services.